Pendekatan Diagnosis dan Tatalaksana Septic Arthritis - Riko Febrian Kunta Adjie (Cermin Dunia Kedokteran, 2018)
Septic arthritis yang disebabkan infeksi bakteri memerlukan kecepatan dan ketepatan diagnosis untuk mengurangi prognosis buruk. Diagnosis pasti tergantung isolasi patogen dari cairan sendi. Tujuan utama tatalaksana adalah sterilisasi sendi, dekompresi sendi, dan melindungi fungsi sendi. Sterilisasi dengan antibiotik intravena minimal 2 minggu, dilanjutkan sesuai hasil kultur. Dekompresi sendi dapat dicapai dengan beberapa metode termasuk aspirasi jarum, arthrotomy, dan arthroscopy.   Septic arthritis caused by bacterial infection reRuired diagnostic speed and accuracy to improve prognosis. Final diagnosis rests on isolation of pathogen from joint fluid. The main management objectives are joint decompression, joint sterilization, and to reserve joint function. Sterilization with empirical intravenous antibiotic for at least 2 weeks, then adjusted based on bacterial culture result. Joint decompression can be achieved by various methods including closed-needle aspiration, tidal irrigation, arthroscopy, and arthrotomy.